Determination of arms and legs contribution to propulsion and percentage of coordination in backstroke swimming - Shahbazi-Moghaddam, M. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
In the present study, the Indirect Measurement of Active Drag (IMAD) was used to study the contribution of the legs and arms to propulsion in backstroke swimming. Contrary to MAD (Measuring of Active Drag) system, the IMAD can be used for all strokes and enabled us to study the backstroke and to estimate not only the percentage of legs` contribution to propulsion but also the arms contribution and whereas the percentage of swimmers` arms and legs co- ordinations. The method revealed that there were good correlations between arms and full strokes forces and velocities. The swimmers` mass did not much correlate with swimmers` velocities but with the forces.